Sr(Ti1-xFex)O3-[delta] film fabrication for photocatalytic applications - Wang, Lulu. (2008)
Photocatalytic reaction is drawing more and more attentions nowadays. This technology aims to effectively utilize clean, safe, and abundant solar energy to achieve complete mineralization of the pollutants into a harmless compound. In this project, we aim to study the synthesis of precursors and fabrication of thin films using sol-gel approach. The thermal behavior and the microstructure of the material were investigated using Thermogravimetric Analysis and Differential Thermal Analysis (TGA/DTA), X-ray Diffractions (XRD), Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). The characterization of the films includes contact angle measurement to deduce the wettability of the film surface. Photocatalytic reaction of thin film and powder was characterized using a photocatalytic reactor under UV illumination.